PEMBANGUNAN POMPA PENDORONG AIR EMBUNG GRIGAK TENAGA SURYA UNTUK PENGAIRAN PERKEBUNAN ECO CAMP MANGUN KARSA - Iswanjono Iswanjono; Tjendro Tjendro; Martanto Martanto; YB Lukiyanto; RB Dwiseno Wihadi; Sudi Mungkasi (Universitas Sanata Dharma, 2022)
In the Mangun Karsa eco camp area, Gunungkidul, Yogyakarta, a reservoir has been built to be used to collect rainwater and named the Grigak Reservoir. The water from the reservoir will be used to irrigate plantation crops grown in the area. However, due to the location of the reservoir under plantation land, a water pump was needed to lift it. Due to the absence of a PLN electricity source and previously built a solar water pump, so to lift the water from the reservoir, a similar solar water pump was built. The water pump used was a jet pump type with a total head of up to 100m. The average water discharge produced at a height of 40m was 27lpm.